A PAPR Reduction Method With EVM Constraints for OFDM Systems - Yajun Wang; Mengmeng Wang; Zhibin Xie (IEEE Access, 2019)
In orthogonal frequency division multiplexing (OFDM) systems, high peak to average power ratio (PAPR) is one of its core issues. The OFDM signal with high PAPR passes high-power amplifier (HPA) will result in severely nonlinear distortions, which not only decreases HPA power efficiency, but also increases the whole system's bit error rate (BER). In order to attain the OFDM signal with lower PAPR and better BER, we consider PAPR optimization with error vector magnitude (EVM) constrains in this paper. Different from the second order conic programming (SOCP) scheme with high complexity proposed in the literature, we present an innovative approach based on linearized alterative direction method of multipliers (LADMM) to deal with the PAPR optimization. The proposed LADMM algorithm is a simple and efficient method with FFT/IFFT complexity in every iteration. We also prove LADMM algorithm's convergence and then perform simulations. Simulation results demonstrate that LADMM algorithm not only acquires larger PAPR reduction, but also obtains better BER.